Interior feedback stabilization of wave equations with time dependent delay - Serge Nicaise; Cristina Pignotti (Electronic Journal of Differential Equations, 2011)
We study the stabilization problem by interior damping of the wave equation with boundary or internal time-varying delay feedback in a bounded and smooth domain. By introducing suitable Lyapunov functionals exponential stability estimates are obtained if the delay effect is appropriately compensated by the internal damping.